Coronary stent technology: a narrative review. Issue 6 (19th September 2016) - Chen, Daniel; Jepson, Nigel
Summary: Coronary angioplasty and coronary artery stents have revolutionised interventional cardiology. Contemporary coronary stent technology continues to seek to improve on the outcomes of the preceding generation of devices by refining their design, structure and component materials. These technologies include new generations of drug‐eluting stents, non‐polymeric stents, bioresorbable polymer‐coated stents, and fully bioresorbable scaffolds. This review discusses the evolution of coronary stent technology, the efficacy and safety of currently available devices, and the rationale for new generation platforms as efforts continue to design the ideal coronary stent technology.